Tests and Proofs : 11th International Conference, TAP 2017, Held as Part of STAF 2017, Marburg, Germany, July 19-20, 2017, Proceedings /: 11th International Conference, TAP 2017, Held as Part of STAF 2017, Marburg, Germany, July 19-20, 2017, Proceedings. (2017) - Unknown
No abstract available